Agenda 2030 for sustainable development and the future of adult learning in Europe - Rebelo, Fernanda (2022)
The 2030 Agenda for Sustainable Development proclaimed in September 2015, on the occasion of the seventieth anniversary of the United Nations, established a set of 17 universal and transformative Goals and targets for our planet and the people who inhabit it, in pursuit of prosperity and peace. Putting this plan into action with a view to its full implementation by 2030 implies a huge collective effort, a collaborative partnership of all countries and entities. Everyone recognises the need to ensure respect for the human rights of all and sustainable development in its three dimensions - economic, social and environmental. If in the environmental dimension, we are faced with the issues of climate change and the limitation of natural resources; at the economic level, the dissemination of information and communication technologies, scientific and technological innovation, automation and artificial intelligence systems are gaining importance; the social challenges cause even more concern today due to Brexit, migration flows, as well as the current movement of refugees and displaced persons fleeing the theatre of war, destruction and death. In the present study we were interested in highlighting Goal 4 of the 2030 Agenda which aims to ensure inclusive and equitable quality education, and promote lifelong learning opportunities for all. The method consisted of a theoretical and descriptive approach based on the principles of the United Nations Charter, the Universal Declaration of Human Rights and relevant international human rights instruments, namely the European Association for the Education of Adults (EAEA). In addition, a quantitative analysis of significant data recently released by Eurostat was carried out. The results show that the working-age population is expected to fall by 5% by 2030, from around 66% to just over 60% of the total population. And that, although there is a trend in the European Union to increase the retirement age, it is thought that such a measure will not be sufficient to solve the problems arising from demographic change. Furthermore, this decrease of active citizens contributing to social security could be compensated through the education of adult immigrants, in those areas where there are greater labour shortages, adjusting their training skills to the market and offering specialisation and language learning opportunities. In this continuous learning may lie the key to solving the problems arising from changes in demography, the fall in the working population and the sustainability of social security. In this sense, a reflection was made on the evolving dimensions of the right to education. In particular, we were interested in the role that adult education can play in the future of Europe. The results obtained show that education in this age group provides European citizens with the necessary and appropriate skills and knowledge to become more responsible and active players, committed to sustainable and inclusive development that respects the values we want to preserve and pass on to new generations. We conclude that adult education enables knowledge recycling, updating and innovation in the labour market, while contributing to the personal fulfilment of the individual, their well-being and the construction of a fairer and more sustainable society.